Comparison of Serum Potassium, MagnEsium, and Calcium Levels between Kanamycin and Capreomycin-BASEd Regimen-Treated MultiDrug-Resistant TuBerculosis Patients in Bandung (CEASE MDR-TB): A Retrospective Cohort Study - Arto Yuwono Soeroto; Guntur Darmawan; Rudi Supriyadi; Panji Gugah Bhaskara; Prayudi Santoso; Bachti Alisjahbana; Ida Parwati (International Journal of Microbiology)
Treatment of multidrug-resistant tuberculosis (MDR-TB) with second-line injectable drugs may result in an electrolyte imbalance. This retrospective study was performed to compare and evaluate the effect of kanamycin and capreomycin on serum potassium, calcium, and magnesium in the first and second month treatment at a tertiary, top-referral hospital in Bandung, Indonesia. Data from 84 subjects with complete medical records of at least serum potassium during either kanamycin-based or capreomycin-based treatment were retrieved from the institutional database. Among these, 53 subjects had complete serum calcium data and 53 subjects had complete serum magnesium data. After the first month of MDR-TB treatment, there was a significant decrease in mean serum potassium (4.0 ± 0.4 mEq/L to 3.7 ± 0.5 mEq/L, p<0.003) in the kanamycin-based group and (4.1 ± 0.5 mEq/L to 3.2 ± 0.6 mEq/L, p<0.001) in the capreomycin-based group. Serum potassium levels were significantly lower in the capreomycin-based group than in the kanamycin-based group (3.2 ± 0.6 mEq/L vs 3.7 ± 0.5 mEq/L, p<0.001). The incidence of hospitalization and requirement for a change in the treatment regimen due to electrolyte imbalances were higher in the capreomycin-based group. No previous longitudinal study has evaluated serum potassium, magnesium, and calcium from the first month of MDR-TB treatment with either kanamycin-based or capreomycin-based regimens. Our findings emphasize the importance of routine monitoring of serum potassium, magnesium, and calcium during MDR-TB treatment, and that more attention should be paid when treatment is given using the capreomycin-based regimen. Moreover, our study supported the 2018 World Health Organization treatment guideline recommendations for removal of kanamycin and capreomycin from the MDR-TB regimens.